Termination of employment without an official letter: A juridical review of employee protection under the manpower act and the job creation act - Lingga, Ebenni; Siregar, Hisar (Priviet Social Sciences Journal, 2025)
This Study Carefully Examines the legal validity  of the protections and guarantees provided by the laws of employees who may lose their jobs without receiving formal written notice. There is a notable disparity: despite the regulatory framework (Law 13/2003,Law 6/2023 on job creation,and PP 35/2021) expressly requiring written procedures, unilateral verbal dismissal remains common. These acts essentially constitute the legal principle,the protective principle (in favorem laboris),and the procedural justice doctrine. Using statutes,conceptual, comparative,and case approaches, this study employs a normative legal methodology. This study focuses on the particular factual case of Novita Sari Naibaho. This analysis is further supported by a review of pertinent jurisprudence to analyze the legal implications,particularly the Serang Industrial Relations Court decision(No.21/Pdt. Sus-PHI/PHI/2025/PN.SRG). The discussion shows that the absence of a formal written notification renders the entire termination process invalid. This study concludes that any dismissal that does not comply with this crucial formal requirement is illegal. In the absence of a final,legally binding court decision,it is implied that the employment relationship is continuous, and the employee retains their full entitlement to all normative rights.